Superconducting gap and pseudogap: Pseudogap - Deutscher, Guy (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The discovery of the pseudogap has been a fundamental advance in uncovering the new physics of the high-Tc cuprates. Yet, its meaning is still far from being clear. In particular, its relation to the superconducting gap remains an object of controversy. While many authors consider that it is a high temperature precursor of superconductivity, which turns into the superconducting gap at low temperatures, others contend that it is a normal state property related only indirectly to superconductivity. We review a number of experiments such as single particle tunneling, Andreev–Saint–James reflections and others, and conclude that in the underdoped regime there exists considerable evidence for the existence of two distinct energy scales, the superconducting gap and the pseudogap, which appear to merge into one another in overdoped samples.